Artificial Intelligence: Solusi Pembelajaran Era Digital 5.0 - Anas, Iqbal; Zakir, Supratman (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
This research discusses Digital Era 5.0 learning solutions, namely the benefits that can be provided by the presence of artificial intelligence in the development of science and technology. Artificial intelligence (AI) is a computer program designed and built to mimic human intelligence, including decision-making ability, logic, and other characteristics of intelligence. Artificial intelligence as a learning solution for the digital era 5.0 is here to improve teaching and learning and innovation in learning implementation. The results of this research show that AI support is needed in the world of education and learning, including for personalized learning, this system can analyze the strengths and weaknesses of students to provide material that suits their level of understanding. AI can also be utilized as real time feedback in learning, also utilized for interactive teaching, data management and administration in education and teaching, as a virtual tutor. AI can also be used for fraud detection and 21st century skills development. AI as an access to education is implemented in the form of distance learning can be in the form of e-learning, learning curriculum development and can simplify and ease the burden that teachers can do in the learning process.